The spatial structure of lithic landscapes : the late holocene record of east-central Argentina as a case study - Barrientos, Gustavo (2015)
Fil: Barrientos, Gustavo. División Antropología. Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata; Argentina